Perioperative Fluid Management in the Enhanced Recovery after Surgery (ERAS) Pathway - Zhu, Alyssa Cheng-Cheng; Agarwala, Aalok; Bao, Xiaodong (Clinics in Colon and Rectal Surgery, 2019)
Fluid management is an essential component of the Enhanced Recovery after Surgery (ERAS) pathway. Optimal management begins in the preoperative period and continues through the intraoperative and postoperative phases. In this review, we outline current evidence-based practices for fluid management through each phase of the perioperative period. Preoperatively, patients should be encouraged to hydrate until 2 hours prior to the induction of anesthesia with a carbohydrate-containing clear liquid. When mechanical bowel preparation is necessary, with modern isoosmotic solutions, fluid repletion is not necessary. Intraoperatively, fluid therapy should aim to maintain euvolemia with an individualized approach. While some patients may benefit from goal-directed fluid therapy, a restrictive, zero-balance approach to intraoperative fluid management may be reasonable. Postoperatively, early initiation of oral intake and cessation of intravenous therapy are recommended.
Keywords: Enhanced Recovery after Surgery; fluid management; goal-directed fluid therapy